Impact of exhaustive exercise on autonomic nervous system activity: insights from HRV analysis - Wang, Weichao; Shao, Mingrui; Du, Weiping; Xu, Yanjun (Frontiers in Physiology, 2024)
IntroductionExhaustive exercise is a common training method in sports, but its impact on the autonomic nervous system of the human body remains unclear. Understanding the effects of exhaustive exercise on the body and its connection with the autonomic nervous system and central nervous system is crucial for guiding healthy training methods.MethodsTwenty-three participants were selected, and exhaustive exercise intervention was performed using the Bruce Protocol. By measuring heart rate variability (HRV), the effects of exhaustive exercise on the autonomic nervous system function were analyzed.ResultsAfter exhaustive exercise, time-domain indices SDNN, RMSSD, and PNN50 all significantly decreased, with changes reaching significant levels (p < 0.01). Among them, the decrease in pNN50 was particularly pronounced, with a change rate of −94.55%. Frequency-domain indices VLF, LF, and HF also showed significant decreases (p < 0.01), but the ratio of LF to HF showed an upward trend (p < 0.01), with LF showing a greater decrease. Nonlinear indices SD1 and SD2 showed extremely significant decreases (p < 0.01), and the SD2/SD1 ratio showed a significant increase (p < 0.01), indicating significant changes in HRV nonlinear characteristics after exercise.DiscussionExhaustive exercise leads to a decrease in autonomic nervous system activity and an increase in sympathetic nervous system activity. These findings underscore the profound impact of exhaustive exercise on the autonomic nervous system, with implications for understanding the physiological responses to intense physical exertion. Further research is warranted to explore the long-term effects of exhaustive exercise on autonomic regulation and its potential implications for training methodologies and athlete health.